Micro-Electro Discharge Machining: Principles, Recent Advancements and Applications, Volume II - Fassi, Irene; Modica, Francesco (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The second volume of the Special Issue on "Micro-Electro Discharge Machining: Principles, Recent Advancements and Applications" confirms the growing interest in the micro-EDM technology as a suitable and efficient technology for machining novel, multilateral components, with demanding requirements in terms of precision, accuracy, and productivity.This volume consists of 10 original research papers which involve several approaches to micro-EDM and cover the enhancement of the process performance, such as the material removal rate, surface roughness, or machining accuracy, using advanced optimization methods. Some studies also consider several dielectric fluid additives and investigate the processability of new materials. Others investigate the combination of Reverse-micro-EDM with laser beam micromachining or explore new applications for the micro-EDM for fabricating antimicrobial nanosilver colloid.